Synergistic use of NMR computation and quantitative interproton distance analysis in the structural determination of neokadcoccitane A, a rearranged triterpenoid featuring an aromatic ring D from Kadsura coccinea. Issue 10 (4th April 2019) - Xu, Hou-Chao; Hu, Kun; Shi, Xiao-Huo; Tang, Jian-Wei; Li, Xiao-Nian; Sun, Han-Dong; Puno, Pema-Tenzin
Abstract : A novel lanostane triterpenoid possessing an aromatic ring D, along with two novel norlanostane triterpenoids, were isolated from Kadsura coccinea . Abstract : Neokadcoccitane A (1 ), an unprecedented 14(13 → 12):28(14 → 8)-diabeo-3, 4-secolanostane triterpenoid possessing an aromatic ring D and an unusual Me-21 orientation, along with two novel 14(13 → 12)-abeo-3, 4-seco-norlanostane triterpenoids featuring three- and one-carbon degradation, respectively (2 and3 ), were isolated from the roots of Kadsura coccinea . The absolute configuration of1 was determined by the synergistic use of NMR computation, quantitative interproton distance analysis, and TDDFT ECD calculation, while that of2 was established using X-ray diffraction.1 was found to exhibit moderate anti-platelet aggregation activity.